2008
DOI: 10.1097/qai.0b013e31816649a4
|View full text |Cite
|
Sign up to set email alerts
|

Description of a “Trans-Saharan” Strain of Human T-Lymphotropic Virus Type 1 in West Africa

Abstract: The aim of this study was to assess the prevalence and the molecular epidemiology of human T-lymphotropic virus type 1 (HTLV-1) in a group of pregnant women living in Guinea Bissau. We studied 427 consecutive pregnant women attending 10 centers for HIV-1 infection monitoring in Bissau. HTLV-1 infection was found in 2.6% of the patients. Phylogenetic analysis of the long terminal repeat region showed that 10 isolates were of the cosmopolitan subtype (HTLV-1a) and that only 1 was of the widespread Central Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…In this study, HIV and HTLV-1 infections showed a cross-sectional association, as has been shown before in this study area in 1990 [25] and in the general adult population [16,41], elderly people [10], an occupational cohort [42] and pregnant women [43] in Bissau. Why this association is stronger for women than for men remains unclear.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, HIV and HTLV-1 infections showed a cross-sectional association, as has been shown before in this study area in 1990 [25] and in the general adult population [16,41], elderly people [10], an occupational cohort [42] and pregnant women [43] in Bissau. Why this association is stronger for women than for men remains unclear.…”
Section: Discussionsupporting
confidence: 74%
“…Within the latter subtype, one large transcontinental clade (a-TC) and three geographically restricted clades were identified: we named these the Senegalese (aSen), North African (a-NA), and West African (a-WA) clades. Of note, the a-Sen group has previously been described and named "trans-Saharan" or "clade N" (within the subgroup HTLV-1a D) (23,24).…”
Section: Resultsmentioning
confidence: 99%
“…35 Likewise, subgroup D has previously been found in Africans, including subjects from Algeria and Guinea Bissau. 36 Finally, we identified a young boy from East Africa living in Spain infected with a new HTLV-1 subgroup within the Cosmopolitan subtype A, which we potentially nominated as subgroup F. To confirm this new subgroup it would be important to get more HTLV-1-infected samples from the Ethiopian population to investigate the molecular epidemiology of this virus in that region.…”
Section: Discussionmentioning
confidence: 99%